Correlation between the Total Dose of Follicle-Stimulating Hormone and Cumulative Live Birth Rate in Women Undergoing in Vitro Fertilization - Long Ho Le; Ngoc Anh Vu Ho; Toan Duong; Manh Tuong Ho; Ngoc Lan Vuong (Fertility & Reproduction, 2024)
Background: Follicle-stimulating hormone (FSH) is widely used during assisted reproductive therapy to facilitate the development of multiple follicles. In turn, the number of oocytes retrieved has been shown to relate to the live birth rate. This retrospective study investigated the correlation between the total FSH dose used and the cumulative live birth rate in individuals who had undergone in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Methods: This retrospective study included women undergoing IVF/ICSI using a gonadotropin-releasing hormone antagonist protocol who had a regular menstrual cycle and an expected normal response to ovarian stimulation. Cumulative live birth rate was defined as the first live birth following the use of all fresh and frozen transfers of embryos derived from one stimulated IVF/ICSI cycle. Results: The analysis included 7,130 stimulated cycles in 6,517 individuals (9,138 transfers). The mean age, antral follicle count, and anti-Müllerian hormone level were [Formula: see text], [Formula: see text], and [Formula: see text][Formula: see text]ng/ml, respectively. The mean total FSH dose, total number of oocytes retrieved, and total FSH dose per oocyte retrieved were [Formula: see text] IU, [Formula: see text], and [Formula: see text] IU, respectively. There was a significant negative correlation between the total FSH dosage and the cumulative live birth rate in women aged [Formula: see text] years ([Formula: see text], 95% confidence interval [−0.14, −0.08]; [Formula: see text]) and in those aged [Formula: see text] years ([Formula: see text], 95% confidence interval [−0.11, −0.02]; [Formula: see text]). Conclusions: The cumulative live birth rate decreased as the total FSH dose increased. These findings suggest that physicians may wish to avoid prescribing a high dose of FSH in women undergoing IVF/ICSI who are predicted not to have a poor response.